2021
DOI: 10.1007/s10637-020-01047-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pharmacokinetics of entrectinib and its active M5 metabolite in healthy volunteers and patients with solid tumors

Abstract: SummaryBackground: Entrectinib is an oral, CNS-active, potent inhibitor of tyrosine receptor kinases A/B/C, tyrosine kinase ROS proto-oncogene 1, and anaplastic lymphoma kinase approved for use in patients with solid tumors. We describe 3 clinical studies, including one investigating the single/multiple dose pharmacokinetics of entrectinib in patients and two studies in healthy volunteers investigating the absorption/distribution/metabolism/excretion (ADME) of entrectinib, its relative bioavailability, and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
(16 reference statements)
0
23
2
Order By: Relevance
“…( B ) Graphs depicting cell viability of OV-054 DSRCT (blue) and the two Ewing sarcoma models (gray), upon a 5-day incubation with different drug concentrations (µM). Known plasma concentrations are shown with the vertical dashed line [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Figurementioning
confidence: 99%
“…( B ) Graphs depicting cell viability of OV-054 DSRCT (blue) and the two Ewing sarcoma models (gray), upon a 5-day incubation with different drug concentrations (µM). Known plasma concentrations are shown with the vertical dashed line [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Figurementioning
confidence: 99%
“…The pharmacokinetics of entrectinib in adult patients with solid tumours, like those of its major active metabolite, M5, are linear [20,33] and not dose-or time-dependent [20]. Peak plasma concentrations of entrectinib and M5 were seen ≈ 4-6 h following single and multiple doses of oral entrectinib in the fed state; steady-state concentrations of entrectinib and M5 were reached within 2 weeks [34]. The estimated steady-state accumulation ratios for entrectinib and M5 were 1.89 and 2.01, respectively [20,33].…”
Section: Pharmacokinetic Properties Of Entrectinibmentioning
confidence: 99%
“…Entrectinib is metabolized primarily by cytochrome P450 (CYP) 3A4 (≈ 76%) to M5; it is also conjugated by uridine 5′-diphospho-glucuronosyltransferase 1A4 to its N-glucuronide conjugate (M-11) [20]. Entrectinib is predominantly eliminated through hepatic metabolism; renal clearance has a minor role [83% of a radiolabelled oral dose was excreted in faeces (36% as unchanged entrectinib; 22% as M5); 3% was excreted in urine] [20,34]. The estimated apparent clearances of entrectinib and M5 are 19.6 and 52.4 L/h, respectively; the estimated elimination half-lives are 20 and 40 h, respectively [20].…”
Section: Pharmacokinetic Properties Of Entrectinibmentioning
confidence: 99%
“…Other, more minor pathways of metabolism included direct glucuronidation (M11) as well as N-oxidation and benzyl hydroxylation by CYP enzymes. Together these additional routes accounted for < 25% metabolism in vitro and none of the products were major circulating metabolites except M11 [7]. As M11 is a glucuronide conjugate which is not expected to show pharmacological activity, further in vivo examination Table 4 Summary of midazolam and 1'-hydroxymidazolam plasma pharmacokinetic parameters with and without coadministration of single and multiple dose entrectinib (600 mg/day) following a single 7.5 mg midazolam dose AUC inf area under the plasma concentration-time curve extrapolated to infinity, C max maximum plasma concentration, ND not done, t 1/2 terminal elimination half-life, T max time of maximum plasma concentration a Unadjusted geometric means (geometric coefficients of variation) for all except T max which is median (minimum, maximum) b Maximum value was due to one outlying subject Unadjusted' refers to raw data, and 'adjusted' refers to data that have been subjected to statistical analysis.…”
Section: Entrectinib As a Victim Of Ddismentioning
confidence: 95%
“…In a mass balance study, entrectinib has been shown to be mainly eliminated through hepatic clearance, with negligible renal clearance (< 1% of the dose is excreted unchanged in urine) [ 7 ]. There are two major circulating metabolites of entrectinib in humans, M5 and M11, contributing 12% and 19%, respectively, of total circulating radioactivity.…”
Section: Introductionmentioning
confidence: 99%